Bahasa Makian untuk Fungsi Keakraban di Kalangan ‘Anak Muda’ Minangkabau - Ike Revita; Nurul Fathiya (Lingua: Jurnal Bahasa, Sastra dan Pengajarannya)
Swear word is commonly regarded as impolite because in a particular situation, it may insult others. However, the swear word may indicate intimacy. It is depicted by the youth in Minangkabau society who use this swear word to keep the relationship closer and intimate. This study aims at identifying the forms of the swear words used by the youth in Tanah Datar Regency, Sumatera Barat. The research is descriptively done. The data are any utterances containing the swear words used by the youth in Tanah Datar Regency, Sumatera Barat. There were around sixty adolescents aged between 18-25 years as the respondents. The data were taken when these adolescents communicating in the cafe, lapau (traditional cafe in Minangkabau), and some other informal places by recording and note-taking the interaction. The interview was also conducted to ensure the swear words used and the meaning.   The analysis is conducted by using the concept of swear words and speech acts. After analyzing the data, it is found that the youth of Minangkabau used four forms of swear words in their communication. They are 1) animal, 2) disability, 3) activity, 4) dirt, and 5) disease. The animal is mostly used because it is in line with the philosophy of Minangkabau people that is learning from nature. The animal is part of nature considered despicable that its behavior should not be imitated.